2020
DOI: 10.1123/jpah.2019-0338
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Physical Factors Associated With Physical Functioning for Patients Receiving Dialysis: A Systematic Review

Abstract: Background: Patients receiving dialysis have reduced physical function, which is associated with unfavorable clinical outcomes and decreased quality of life. The authors aimed to identify and explore modifiable physical factors associated with physical function for patients receiving dialysis. Methods: Searches were performed in MEDLINE, Embase, Ovid Emcare, and The Cochrane Library in October 2018. Etiological studies involving dialysis populations that report association or predictive statistics between a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 78 publications
1
9
0
4
Order By: Relevance
“…In this study, we observed that there are far more men than women with COVID-19 in HD patients who are in line with the previous study on general population. This is due to the fact that the number of women in HD is lower than the men (13:18), and the women have sex hormones and X chromosome, which can regulate adaptive and innate immunity [7]. In addition, most HD patients infected with COVID-19 were mainly the elderly and those with other chronic diseases besides renal failure which is in line with the previous study, but the average age and odds of chronic disease were higher [7].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, we observed that there are far more men than women with COVID-19 in HD patients who are in line with the previous study on general population. This is due to the fact that the number of women in HD is lower than the men (13:18), and the women have sex hormones and X chromosome, which can regulate adaptive and innate immunity [7]. In addition, most HD patients infected with COVID-19 were mainly the elderly and those with other chronic diseases besides renal failure which is in line with the previous study, but the average age and odds of chronic disease were higher [7].…”
Section: Discussionsupporting
confidence: 84%
“…This is due to the fact that the number of women in HD is lower than the men (13:18), and the women have sex hormones and X chromosome, which can regulate adaptive and innate immunity [7]. In addition, most HD patients infected with COVID-19 were mainly the elderly and those with other chronic diseases besides renal failure which is in line with the previous study, but the average age and odds of chronic disease were higher [7]. This may be because the HD patients had older average age, more complications, and weaker immunity than the general population [6].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle function declines at a rate different from that of muscle size [ 24 ], and the worse physical function of patients on HD compared to non-CKD elderly was not explained by muscle size [ 22 ]. Nonetheless, a recent systematic review discusses how the association between physical function and muscle size in CKD patients is still controversial [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and severity of symptoms are associated with lower QoL [ 5 ]. Non-pharmacological strategies to improve QoL that consider patients’ symptoms are focused on some defined type of symptoms, either related to physical functioning (e.g., improving muscle strength through exercise) [ 9 ] or psycho-emotional (e.g., decreasing depressive and anxious symptoms through psychological interventions) [ 10 ]. Those interventions are effective for their therapeutic target [ 11 ] and involve some degree of active patient’s participation, but they often do not consider the patient’s perspective about their own ability to cope with multiple stressors inherent to their disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%